PENGARUH ENVIRONMENTAL RISK TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi pada perusahaan-perusahaan di Indonesia, Singapura, Malaysia, Thailand, Filipina dan Vietnam) - Nuzula, Nila Firdausi; Damayanti, Cacik Rut; Sulasmiyati, Sri (Profit: Jurnal Adminsitrasi Bisnis, 2019)
The purpose of this study was to find out how the influence of environmental risk on profitability and the value of companies that are publicly listed on stock exchanges in Indonesia, Malaysia, Singapore, Thailand, the Philippines and Vietnam. This study uses secondary data for all variables, namely utilizing data from Osiris Financial Database, which includes 558 companies from these six countries. The results of the study show that environmental risk is not proven to affect financial performance, both for accounting or market-based financial indicators in Indonesia, Malaysia, Singapore, Thailand and the Philippines. Environmental risk proved to significantly affect Price to Earnings Ratio in Vietnam, both in testing univariate and multivariate regression models with several control variables. However, in multivariate testing by including control variables, it is evident that environmental risk has a real impact on achieving ROA in Singapore and Thailand, on ROE in Malaysia and Vietnam, on PER in Thailand and Vietnam, and Tobin's Q on companies in Indonesia, Malaysia, and Thailand. Multivariate testing with combined data from six countries shows that environmental risk together contributes significantly to achieving ROA and PER. Control variables that contribute to the significant influence are industry type, country of origin, and size of the company.Â